2016
DOI: 10.2147/tcrm.s104942
|View full text |Cite
|
Sign up to set email alerts
|

Occupational HIV risk for health care workers: risk factor and the risk of infection in the course of professional activities

Abstract: Virtually created panic among health care workers about pandemic acquired immune deficiency syndrome prompted us to review the scientific literature to investigate the risk of human immunodeficiency virus (HIV) transmission in the daily works of health care workers, especially surgeons and anesthesiologists. In this review, we report worldwide valuations of the number of HIV infections that may occur from unsafe daily work in health care. We also present how to minimize the risk of infection by taking precauti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
(28 reference statements)
0
8
0
1
Order By: Relevance
“…According to the UNAIDS 2019 report, the world is on course to stop the AIDS epidemic by 2030, but Pakistan is one of the nations where the ratio of new AIDS cases has increased dramatically [ 3 , 4 ]. Thus, studies elaborating on the knowledge, attitude and practices of HCPs—being at high-risk—towards HIV post-exposure measures are warranted [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the UNAIDS 2019 report, the world is on course to stop the AIDS epidemic by 2030, but Pakistan is one of the nations where the ratio of new AIDS cases has increased dramatically [ 3 , 4 ]. Thus, studies elaborating on the knowledge, attitude and practices of HCPs—being at high-risk—towards HIV post-exposure measures are warranted [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the respondents believed, regarding the nature of occupational expose to HIV-infected blood, that the highest possibility for the spread of infection is a percutaneous injury (43.1%), whereas 23.8% and 16.2% opined that skin contact with HIV-infected blood and a mucous membrane exposure, respectively, pose the greatest risk for infection transmission. One more study reported that the threat of transmission of HIV infection associated with percutaneous contact with infected blood is ~0.3% for every exposure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women who works in hazardous environment without protective equipment could contribute to the increment of HIV prevalence for the employed patients [ 25 ]. In addition other study stated that HIV infection is associated with some occupations like health care workers like surgeons, anesthetist, and physicians engaged in invasive procedures [ 26 ]. This could indicate that employed in unsafe work environment might be associated with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In most situations, PEP will be immediately stopped after obtaining negative results, avoiding any potential side effects. PEP cannot prevent the infection, but it can limit virus replication by preventing viral DNA from being incorporated into host DNA [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%